Search for the standard model Higgs boson produced through vector boson fusion and decaying to b(b)over-bar - (:unkn) unknown (AMER PHYSICAL SOC, 2015)
A first search is reported for a standard model Higgs boson (H) that is produced through vector boson fusion and decays to a bottom-quark pair. Two data samples, corresponding to integrated luminosities of 19.8 fb(-1) and 18.3 fb(-1) of proton-proton collisions at root s = 8 TeV were selected for this channel at the CERN LHC. The observed significance in these data samples for a H -> b (b) over bar signal at a mass of 125 GeV is 2.2 standard deviations, while the expected significance is 0.8 standard deviations. The fitted signal strength mu = sigma/sigma(SM) = 2.8(-1.4)(+1.6). The combination of this result with other CMS searches for the Higgs boson decaying to a b-quark pair yields a signal strength of 1.0 +/- 0.4, corresponding to a signal significance of 2.6 standard deviations for a Higgs boson mass of 125 GeV.
Keywords: SYMMETRIES